A history of lesbian politics and the psy professions. (February 2021) - Spandler, Helen; Carr, Sarah
This article explores the relationship between lesbian activists and the "psy professions" (especially psychology and psychiatry) in England from the 1960s to the 1980s. We draw on UK-based LGBTQIA+ archive sources and specifically magazines produced by, and for, lesbians. We use this material to identify three key strategies used within the lesbian movement to contest psycho-pathologisation during this 30-year period: from respectable collaborationist forms of activism during the 1960s; to more liberationist oppositional politics during the early 1970s; to radical feminist separatist activism in the 1980s. Whilst these strategies broadly map onto activist strategies deployed within the wider lesbian and gay movement during this time, this article explores how these politics manifested in particular ways, specifically in relation to the psy disciplines in the UK. We describe these strategies, illustrating them with examples of activism from the archives. We then use this history to problematise a linear, overly reductionist or binary history of liberation from psycho-pathologisation. Finally, we explore some complexities in the relationship between sexuality, activism and the psy professions.